Efficacy of angled metallic fins for enhancing phase change material melting - Qin, Zhen (2022)
Research on enhancing phase change material (PCM) heat transfer is concentrated in latent heat thermal energy storage (LHTES) field, especially with utilization of metallic fins. One interesting fin parameter that was less explored for a rectangular PCM system, is the metal fin's inclined angle. This research aims to experimentally validate the hypothesis and evaluate the efficacy of angled metallic fins enhancing PCM melting in a sidewall heated cuboid LHTES system. Experiments indicate that three-dimensional PCM melting in the LHTES unit can be characterized as two dimensional. The angled fins considerably influence temperature evolution of local solid PCM around fins. Compared to the horizontal fin, positive inclined fins with angles of +30° and +15° prolong the PCM melting time by 4.0% and 3.8% respectively, while the downward tilted inclined fins at −15° and −30° promote PCM melting by up to 5.2% melting fraction difference. Extending simulations with seven fin angles and three fin lengths explicate the substantial effect on PCM heat storage, melting time, and temperature uniformity. Particularly, the longest fin at the downward angle of −15° reduces the PCM melting time most. The study shows feasibility of utilizing downward angled fins to enhance PCM transient melting in the LHTES unit.